(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
This article addresses the issue of effectively organizing AI-based oral speaking exercises in distance ESP education under low-bandwidth internet conditions. The proposed methodological model enables students to develop context-appropriate, reflective, and communicative speaking skills through simplified AI tools. This approach enhances the quality of distance learning and fosters a new stage of digital pedagogy despite technical limitations.